Serious safety events: Getting to Zero™. Issue 3 (18th January 2013) - Hoppes, Michelle; Mitchell, Jacque L.; Venditti, Ellen Grady; Bunting, Jr., Robert F.
Abstract To advance the goal of Getting to Zero and eliminating preventable harm, ASHRM is providing guidance for defining, investigating, and measuring serious safety events. The first step in this process is the recommendation for a common and standardized definition. A common definition for a serious safety event facilitates timely detection, rapid action, and future prevention. This paper outlines that definition, provides a skill‐based model for investigation, and explains a clear plan for how to conduct the investigation. A measurement system is described to determine the frequency of SSEs and comparison methods to determine events prevented, potential lives saved, and methods to demonstrate financial loss control. These methods and approach are consistent with ASHRM's core values and mission, which is safe and trusted healthcare.